2010
DOI: 10.1152/physrev.00061.2009
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Death: A Clear and Present Danger

Abstract: The hepatocyte is especially vulnerable to injury due to its central role in xenobiotic metabolism including drugs and alcohol, participation in lipid and fatty acid metabolism, its unique role in the enterohepatic circulation of bile acids, the widespread prevalence of hepatotropic viruses, and its existence within a milieu of innate immune responding cells. Apoptosis and necrosis are the most widely recognized forms of hepatocyte cell death. The hepatocyte displays many unique features regarding cell death b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
375
2
12

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 419 publications
(405 citation statements)
references
References 304 publications
(370 reference statements)
7
375
2
12
Order By: Relevance
“…The values are shown as mean ± SEM, n = 3. *Significantly different from the untreated control (0 lg/ml) at p \ 0.05 Malhi et al 2010). Our findings presented here, believed to be the first of their kind for breast cancer cells, demonstrate that H. magnifica venom extract induces apoptosis through the activation of caspases.…”
Section: Discussionsupporting
confidence: 45%
“…The values are shown as mean ± SEM, n = 3. *Significantly different from the untreated control (0 lg/ml) at p \ 0.05 Malhi et al 2010). Our findings presented here, believed to be the first of their kind for breast cancer cells, demonstrate that H. magnifica venom extract induces apoptosis through the activation of caspases.…”
Section: Discussionsupporting
confidence: 45%
“…Infection of liver-specific adenoviruses may cause inflammatory responses and initial apoptosis in the infected sites to subsequently recruit innate inflammatory cells including Kupffer cells. As previously reported about hepatocyte cell death 57 , infiltrated Kupffer cells may promote the activation of hepatic stellate cells which further develop into myofibroblasts. The activated myofibroblasts may secrete TGF-b1, which eventually amplify liver apoptosis in the A20 knockdown animal model.…”
Section: Discussionsupporting
confidence: 63%
“…Bile acids play an important role in the enterohepatic system, but the corresponding cytotoxicity to hepatocytes should also be addressed [1,2] . Numerous studies have suggested that the intrahepatic accumulation of bile acids may directly or indirectly cause further damage to the liver [3] . One of the hypotheses regarding the pathophysiology of cholestasis is that accumulated hepatic bile acids directly induce cell apoptosis, as supported by studies on rat hepatocytes and human hepatoma lines [4,5] .…”
Section: Introductionmentioning
confidence: 99%